Terms of providing of equal starting possibilities of receipt of pre-school education (Pedagogy of Higher and Secondary Education, 2013)
Suyatinova K. E. Terms of providing of equal starting possibilities of receipt of pre-school education.In the article an author examines the problem of the following and continuity of education in Ukraine, gives the review of organizational forms of receipt of pre-school education for the children of five-year age, which do not visit preschool establishments. Presents experience collective of establishment, on the base of which it is created kanikulyarno adaptation group and work of konsul'tativnogo point.
Keywords: pre-school preparation; continuous education; succession; forms of preschool education; organization of raboti with the children of five-year age